Factors Affecting the Survival Rate of Dental Implants: A Retrospective Study - Raikar, Sonal (J Int Soc Prev Community Dent, 2017)
AIMS AND OBJECTIVES: Dental implants have emerged as new treatment modality for the majority of patients and are expected to play a significant role in oral rehabilitation in the future. The present study was conducted to assess various factors affecting the survival rate of dental implants. MATERIALS AND METHODS: The present retrospective study was conducted in the Department of Prosthodontics. In this study, 5200 patients with dental implants which were placed during June 2008–April 2015 were included. Exclusion criteria were patients with hormonal imbalance, patients with chronic infectious disease, patients receiving immunosuppressive therapy, pregnant women, drug and alcohol addicts, and patients with severe periodontal diseases. Parameters such as name, age, gender, length of implant, diameter of implant, location of implant, and bone quality were recorded. Data were tabulated and statistically evaluated with IBM SPSS Statistics for Windows, Version 20.0., IBM Corp., Armonk, NY, USA. RESULTS: Out of 5200 patients, 2800 were males and 2400 females. Maximum implants failures (55) were seen in age group above 60 years of age (males – 550, females –700). Age group <40 years (males – 750, females – 550) showed 20 failed implants. Age group 41–60 years (males – 1500, females – 1150) showed 45 failed implants. The difference was nonsignificant (P = 0.21). Maximum implant failure was seen in implants with length >11.5 mm (40/700) followed by implants with <10 mm (20/1650) and 10–11.5 mm (60/2850). The difference was significant (P < 0.05). Maximum implants failure (30/1000) was seen in implants with diameter <3.75 mm followed by implants with diameter >4.5 mm (16/1600) and implants with diameter 3.75–4.5 mm (50/2600). The Chi-square test showed significant results (P < 0.05). Mandibular posterior showed 3.3% implants failure, maxillary posterior revealed 2.2%, maxillary anterior showed 2.1%, and mandibular anterior showed 1% failure rate; this difference was significant (P < 0.05). Type I bone showed 0.3% implant failure, Type II showed 1.95%, Type III showed 3%, and Type IV revealed 0.8% failure rate; this difference was significant (P < 0.05). CONCLUSION: Age, length of implant, diameter of implant, bone quality, and region of implant are factors determining the survival rate of implants. We found that implant above 11.5 mm length, and with diameter <3.75 mm, placed in the mandibular posterior region, in Type III bone showed maximum failures.